A conceptual framework of sport participation and women's empowerment. Issue 5 (3rd September 2017) - Lim, So Youn; Dixon, Marlene A.
ABSTRACT: Sport has the capacity to generate personal change for girls or women. It could be a place where women become empowered and overcome many of the areas of inequitable perceptions or treatment that impact women across the globe. However, sport is not always empowering, safe, or confidence-building. The inconsistent effects of experiences in sport participation are not ubiquitous, nor do they inherently result in positive outcomes [Chalip (2006). Toward a distinctive sport management discipline. Journal of Sport Management, 20, 1–21; Green (2008). Sport as an agent for social and personal change. In V. Girginov (Ed.), Management of sports development (pp. 129–145). Oxford: Elsevier]. However, we know little about how and why some sport experiences are empowering and others are not and what contextual elements of sport and of women's lives affect the empowerment experience through sport. Toward that end, this conceptual study presents a three-tiered framework that integrates psychological empowerment theory into existing literature on sport structure and culture to present new avenues of exploration and analysis regarding the design and implementation of sport programs for girls and women.